Water-mediated adhesion of oil sands on solid surfaces at low temperature. (15th July 2022) - Yang, Qimeng; You, Jae Bem; Tian, Boran; Sun, Shaofeng; Daniel, Dan; Liu, Qi; Zhang, Xuehua
Abstract: Frozen oil sands adhere to the walls of mining fleets in winter, which is an undesirable phenomenon that reduces the delivery capacity of vehicles and wastes fuel for in-land transportation. For automated surface mining, an effective and scalable approach is needed to replace the current method for removing adhered oil sands by shovelling or steam cleaning. In this work, we identify ice formation at the interface of oil sands and the different substrates (steel, rubber, and bitumen/asphaltene coated steel) as the primary reason for the observed high adhesion strength of more than 1, 000 kPa; in absence of ice formation, the adhesion strength of oil sand is smaller than 2 kPa. At temperature of −2.5 °C to −20 °C, the adhesion strength was measured by a force apparatus with thermal control as water content in oil sands matrix was varied from 4 to 14 wt%. The adhesion strength was found to increase linearly with water content. At a fixed water content, the adhesion strength was stronger at a lower temperature after a short freezing time of 5 min. The relationship between water content and the adhesion strength was rationalized by a theoretical model, based on the contact area between ice and the substrate. X-ray micro-computed tomography confirmed that water formed more capillary bridges with the substrate at a higher water content. To effectively reduce the adhesion of oil sands on the substrate, a method was proposed based on anti-icing by spraying a small amount of anti-freezing liquid (0.3 L / m 2 ) on the substrate, which effectively reduced the adhesion strength to < 2 kPa. The insights and proposed anti-freezing approach in this study may be applied to reducing adhesion of not only frozen oil sands, but wet granular materials in general. Highlights: Measure the adhesion strength of frozen oil sands on solid substrates at low temperature. Identify and explain the linear relationship between the adhesion strength and water contents. Visualize air gaps at the interface filled with interstitial water from X-ray microCT. Provide an effective solution to reducing the adhesion of oil sands.